METODE SYARAH HADIS DALAM KITAB AL-MUNTAQA SYARAH AL-MUWATTA’ - Muhammad Qomarullah (Jurnal khabar: Komunikasi dan Penyiaran Islam, 2020)
Research discusses the methodology of the tradition of hadith in the book of al-Muntaqa which is the syarah al-Muwatta 'which the book was written by Al-Baji, nicknamed by jurists and Mutakallimin, writers, poets as "skilled debaters, writers in many sciences, has a lot of knowledge ". This research is a biographical literature study of an al-Baji writer of al-muwatta 'based on a review of the literature of the book that al-Muntaqa explains the traditions of the prophet by describing all aspects which include the traditions in accordance with the tendencies and the expertise of the surrender so called the Tahili method. for example the marriage chapter, which is contained in the book of al-Muntaqa, it can be concluded that this Shari'ah gives a strong exposure to bi al-ma'sur and does not only explain one side of the view.